PENERAPAN TEKNIK AKUPUNTUR KOTA TERHADAP PUSAT OLAHRAGA DAN REKREASI SEBAGAI RUANG KETIGA DI TEPI DANAU SUNTER - Marviera Liandry; Sutrisnowati Machdijar Odang (Jurusan Arsitektur dan Perencanaan, 2022)
Lake Sunter, a sports and recreation center area in Sunter, is determined to be the acupoint in this area. East and West Sunter Lakes are a unit that has a function as a sports and recreation facility which is also adjacent to Gelora Sunter where the building supports indoor sports. As a unified area that has the same function, access for pedestrians is still considered lacking because it is separated by a highway with various types of vehicles passing by. Urban Acupuncture is an approach to provide solutions to problems in urban areas, including the problems found in the Lake Sunter area as a center for sports and recreation. By providing a sports center facility equipped with a